The future of the European natural gas market: a quantitative assessment - Aguilera, Roberto F. (Pergamon, 2010)
The debate over the availability of conventional natural gas has been nearly as strong as that forconventional oil. In Europe, the debate is strengthened due to the region’s dependence on natural gasfrom outside countries. In addition, concern has been expressed by some energy experts in recent years about an imminent shortage of natural gas from Europe, caused supposedly by dwindling natural gas resources. Thus, the purpose of this analysis is to address the concern by assessing the availability of natural gas in the region. This is done by estimating a cumulative availability curve showing natural gas endowment versus production costs. The findings indicate that natural gas in Europe is more available and economic than often assumed. Increased research and development of this potential could help increase energy security in the region.